Mothers Inside and Out? Pseudo-Families and Motherhood in a Women’s Prison - Dillavou, Julia (Crime & delinquency, 2025)
The pseudo-family is a longstanding carceral concept, but its existence and characteristics are uncertain in contemporary women’s prisons. This study explores pseudo-family membership and pseudo-motherhood among 132 women incarcerated in a maximum-security prison. Self-reported data reveal that the pseudo-family remains an active concept in the sampled prison, with over half of the surveyed women reporting prison family membership. Pseudo-mothers are perceived as maternal, supportive, and wise by their pseudo-children. Multivariate OLS and logistic regressions suggest that pseudo-mothers had similar relationship quality with, and visitation from, their biological children, compared to other imprisoned mothers. These findings contribute to our understanding of women’s adaptations to incarceration and have implications for family reunification policies.